Methylmercury modifies temporally expressed myogenic regulatory factors to inhibit myoblast differentiation. (March 2020) - Culbreth, Megan; Rand, Matthew D.
Abstract: Methylmercury (MeHg) is a pervasive environmental toxicant, with known detrimental effects on neurodevelopment. Despite a longstanding paradigm of neurotoxicity, where motor deficits are prevalent among those developmentally exposed, consideration of muscle as a MeHg target has received minimal investigation. Recent evidence has identified muscle-specific gene networks that modulate developmental sensitivity to MeHg toxicity. One such network is muscle cell differentiation. Muscle cell differentiation is a coordinated process regulated by the myogenic regulatory factors (MRFs): Myf5, MyoD, MyoG, and MRF4. A previous study demonstrated that MeHg inhibits muscle cell differentiation in vitro, concurrent with reduced MyoG expression. The potential for MeHg to modify the temporal expression of the MRFs to alter differentiation, however, has yet to be fully explored. Using the C2C12 mouse myoblast model, we examined MRF expression profiles at various stages subsequent to MeHg exposure to proliferating myoblasts. MeHg was seen to persistently alter myoblast differentiation capacity, as myod, myog, and mrf4 gene expression were all affected. Myog exhibited the most robust changes in expression across the various culture conditions, while myf5 was unaffected. Following MeHg exposure to myoblasts, where elevated p21 expression indicated departure from proliferation, cells failed to subsequently differentiate, even in the absence of MeHg, as reflected by a concurrent reduction in MRF4 and myosin heavy chain (MHC), markers of terminal differentiation. Our results indicate that within a brief window of exposure MeHg can disrupt the intrinsic myogenic differentiation program of proliferative myoblasts. Highlights: Methylmercury inhibits C2C12 mouse myoblast differentiation. Temporal myogenic regulatory factor expression is modified with methylmercury exposure. MyoG is most robustly altered by methylmercury in vitro. Acute methylmercury exposure to proliferating myoblasts prevents subsequent cell differentiation.